Modeling the flood flow of the Muraqia River using numerical methods - بشار غانم,; عز الدين حسن , (Latakia University Journal -Engineering Sciences Series, 2023)
The occurrence and spread of floods, especially river floods, leads to great risks and damages from an economic, social and urban point of view, so it is necessary to study the behavior of flow during the flood to mitigate as much as possible from these damages. This research describes the integration of geographic information systems (GIS) with Hec-Ras program in order to build a mathematical model of the flood flow of the Muraqia River. The optimal engineering solutions for organizing and proposing the necessary water structures, and the study concluded to find flooding schemes for the Muraqia River with different possibilities, which will help decision makers to assess the risks resulting from these floods, reduce human and economic losses, develop emergency plans and formulate urban policies.